Hybrid teak/sal wood flour reinforced composites: mechanical, thermal and water absorption properties. (28th September 2018) - Jain, Nitin Kumar; Gupta, M K
Abstract: In present work, effect of sal wood flour hybridization on the mechanical, thermal and water absorption properties of teak wood composite has been investigated. Wood composites were prepared by hand lay-up technique keeping constant 33 wt% of total wood flour content with varying proportion of teak and sal wood flour. Mechanical properties of the wood composites were analyzed by tensile, flexural and impact test. Further, dynamic mechanical properties were also performed in terms of glass transition temperature ( T g ), storage modulus ( E ′) and damping (Tan δ ). Thermogravimetric Analysis was used to measure the degradation of wood composites with respect to temperature. Water absorption properties were carried out in terms of percentage of water absorption at saturation stage, and sorption, diffusion and permeability coefficients. Moreover, morphological analysis of the composites was examined by Scanning Electron Microscope. The results suggested that mechanical, thermal and water resistance properties were significantly enhanced due to hybridization. The best mechanical performance among all composites was exhibited by hybrid wood composite of equal proportion of teak and sal woods.